The Impact of Agricultural Environmental Pollutions on the Population’s Quality of Life. The Experience of Kazakhstan - MUSTAFAYEVA, Bagila; KALTAYEVA, Saule; SAPAROVA, Ainura; ALIMKULOVA, Elvira; KULBAYEVA, Meruert (Journal of Environmental Management and Tourism, 2019)
The purpose of the present study is analyzing the trends of agricultural pollutions and their impact on the health of the population of the Republic of Kazakhstan. The main research methods include a bibliographic review of the literature on the research subject, as well as qualitative and quantitative analysis of statistical indicators of agricultural production development, and the dynamics of agroecological indicators of the Republic of Kazakhstan. To assess the impact of agricultural changes on the quality of life associated with the health of the population, the analysis of secondary data of sociological research conducted by the Environmental Fund of Kazakhstan was carried out. The results of the study show that since 1999 the agriculture of the Republic of Kazakhstan has undergone structural changes which are characterized by active mechanization, intensification, and specialization. At the same time, the widespread use of fertilizers and pesticides, as well as irrigation, the growth of pollution from livestock, and the employment of heavy machinery have adverse effects on water and soil.